Gamification in Indonesian Language Learning: The Use of Bamboozle To Optimize Students Reading and Writting (Literacy) - Pratiwi, Irma Eka; Pertiwi, Cerianing Putri; Anita, Devie Eka Juli (Indonesian Journal of Primary Education, 2024)
This research purposes to determine the students learning results and determine the effect of using bamboozle media on students' reading and writing literacy skills in Indonesian language subjects for class IV at SD Negeri Wungu 01. It used classroom action research through 2 cycles with the Stephen Kemmis and M.C.Taggart model. Data collection tools are observation, test, and documentation. The subjects were class IV consisting of 18 students. Before conducting the research, researchers observed that the students learning results were still not good, this could be observed from the low learning results of students in pre-cycle activity. Based on the results of data analysis, in the pre-cycle activities the percentage of students' learning completion only reached 55% with the number of students who had completed only 3 people while those who had not completed were 15 people, then after applying the bamboozle media within the first cycle the percentage of learning completion students escalated to 69% ,The number of students who have completed it completely is 14 people while those who had not yet completed as many as 4 people, then escalated again in cycle II activities by obtaining 90% with the number of students who had completed as many as 16 people while those who had not yet completed were only 2 people, then the researchers concluded that bamboozle media had an effect on improving student learning results in class IV at SDN Wungu 01.